Optical reflectance of solution processed quasi-superlattice ZnO and Al-doped ZnO (AZO) channel materials. (24th March 2017) - Buckley, Darragh; McCormack, Robert; O'Dwyer, Colm
Abstract: The angle-resolved reflectance of high crystalline quality, c -axis oriented ZnO and AZO single and periodic quasi-superlattice (QSL) spin-coated TFT channels materials are presented. The data is analysed using an adapted model to accurately determine the spectral region for optical thickness and corresponding reflectance. The optical thickness agrees very well with measured thickness of 1–20 layered QSL thin films determined by transmission electron microscopy if the reflectance from lowest interference order is used. Directional reflectance for single layers or homogeneous QSLs of ZnO and AZO channel materials exhibit a consistent degree of anti-reflection characteristics from 30 to 60° (~10–12% reflection) for thickness ranging from ~40 nm to 500 nm. The reflectance of AZO single layer thin films is  <10% from 30 to 75° at 514.5 nm, and  <6% at 632.8 nm from 30–60°. The data show that ZnO and AZO with granular or periodic substructure behave optically as dispersive, continuous thin films of similar thickness, and angle-resolved spectral mapping provides a design rule for transparency or refractive index determination as a function of film thickness, substructure (dispersion) and viewing angle.